2007
DOI: 10.1002/pi.2308
|View full text |Cite
|
Sign up to set email alerts
|

The effect of nanoscale vanadium pentoxide on the electrical and mechanical properties of poly(vinyl alcohol)

Abstract: Poly(vinyl alcohol) (PVA) loaded with vanadium pentoxide (V 2 O 5 ) nanoparticles was successfully prepared at room temperature and ambient pressure. Transmission electron microscopy was used to characterize the final product. It was found that V 2 O 5 nanoparticles were well dispersed and uniform in shape and that the diameter of the particles was confined to within 8 nm. Addition of small amounts (0.2-1 wt%) of nanoparticulate V 2 O 5 to PVA increased the electrical conductivity as well as the modulus of ela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
20
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 93 publications
(25 citation statements)
references
References 18 publications
5
20
0
Order By: Relevance
“…(b) shows the XRD patterns of PVC and PVC loaded with CdO nanoparticles. For pure PVC, the broad peak, halo, in the region of 15–35°, indicates the amorphous nature of PVC . By comparing the XRD pattern of pure PVC with its nanocomposites, it is observed that there is a homogenous distribution of CdO in PVC and the diffraction peaks of CdO are seen clearly starting from the CdO content of 0.7 wt%.…”
Section: Resultsmentioning
confidence: 98%
“…(b) shows the XRD patterns of PVC and PVC loaded with CdO nanoparticles. For pure PVC, the broad peak, halo, in the region of 15–35°, indicates the amorphous nature of PVC . By comparing the XRD pattern of pure PVC with its nanocomposites, it is observed that there is a homogenous distribution of CdO in PVC and the diffraction peaks of CdO are seen clearly starting from the CdO content of 0.7 wt%.…”
Section: Resultsmentioning
confidence: 98%
“…These composites possess unique properties, which do not exist for either inorganic component or polymer alone. Nanocomposites attract considerable attention and comprise a significant part in the field of portable devices because of their low cost, high sensitivity, fast response, and relative simplicity [7–14].…”
Section: Introductionmentioning
confidence: 99%
“…This may be attributed to the enhancement of light propagation into microporous film. The optical band energy gap, E g , for both films were determined based on Tauc's relation for direct electronic transition [24–26]. where α is the absorption, h is Planck's constant, and ν is the incident photons frequency.…”
Section: Resultsmentioning
confidence: 99%